Making enemies with media. Issue 1 (March 2020) - Packer, Jeremy; Reeves, Joshua
This article examines the role of media technology in determining preconstitutive enemies of the political order. To do so, it analyzes how discipline-specific methods of enemy detection, analysis, and neutralization correspond to different media environments. Media have a diagnostic and prescriptive significance: not only do they locate enemies that conform to their own unique standards of measurement, they also offer reprogramming resources that accentuate their own peculiar biases and capacities. Episodes in the history of biology and psychology are examined for evidence of this media logic.